The future role of renewable energy sources in European electricity supply : A model-based analysis for the EU-15 - Rosen, Johannes (KIT Scientific Publishing, 2008)
Ambitious targets for the use of renewable electricity (RES-E) have been formulated by the EU Commission and the EU Member States. Taking into account technical, economic, and ecological framework conditions of the electricity market in a model-based approach, this book provides a comprehensive, quantitative assessment of the future penetration of renewable electricity in the European electricity market.